Upaya Perlindungan Penyu Di Kawasan Ekosistem Esensial Koridor Penyu Pantai Kuranji, Lombok Barat - Wihelmus Jemarut; Kornelia Webliana B; Diah Permata Sari (Fakultas Kehutanan, Universitas Hasanuddin, 2021)
Abstract : In 2017, the government designated Kuranji Beach West Lombok as the Sea Turtle Corridor Essential Ecosystem Area (KEE Kuranji). This is intended to protect the existence of sea turtles in the area. However, the practice of catching and trading sea turtles and or parts of the sea turtles and turtle eggs is still rampant by the people around the area. Based on this, it is necessary to conduct a study with the aim of evaluating the efforts to protect turtles in the KEE of the sea Turtle Corridor, Kuranji Village, West Lombok. This study describes descriptively on the protection of turtles in terms of preemptive, preventive and repressive efforts. This research was conducted from July to August 2019 with data collection using purposive sampling technique. The results showed that the effectiveness of turtle protection in the Kuranji Village area was still low, both at the preemptive stage to raise public awareness, supervision was still minimal (preventive), and there were no efforts to take action against violators (repressive). Based on the search result, there is no data on prosecution for violations of turtle use in the 2017-2019 period, while the results of field observations and interviews with the community show that during this period the practice of selling turtle eggs was rampant.